Changes in lung immune cells related to clinical outcome during treatment with infliximab for sarcoidosis. (22nd April 2020) - Kullberg, S; Rivera, N V; Abo Al Hayja, M; Grunewald, J; Eklund, A
Summary: Pulmonary sarcoidosis is characterized by an exaggerated CD4 + T cell response and formation of non-necrotizing granulomas. Tumour necrosis factor α (TNF-α) is regarded as crucial for granuloma formation and TNF-α inhibitors offer a third-line treatment option for patients not responding to conventional treatment. However, not all patients benefit from treatment, and an optimal dose and treatment duration have not been established. Insight into the influence of TNF-α inhibitors on lung immune cells may provide clues as to what drives inflammation in sarcoidosis and improve our understanding of treatment outcomes. To evaluate the effects of treatment with the TNF-α inhibitor infliximab on lung immune cells and clinical features of the patients, 13 patients with sarcoidosis refractory to conventional treatment were assessed with bronchoalveolar lavage (BAL), spirometry and computerized tomography (CT) scan closely adjacent to the start of infliximab treatment. These investigations were repeated after 6 months of treatment. Treatment with TNF-α inhibitor infliximab was well tolerated with no adverse events, except for one patient who developed a probable adverse event with liver toxicity. Ten patients were classified as responders, having a reduced CD4/CD8 ratio, a decreased percentage of CD4 + T cells expressing the activation marker CD69 and number of mast cells ( P < 0·05 for all). The percentage of T regulatory cells (Tregs ), defined as forkhead box P3 + CD4 + T cells decreased in most patients. In conclusion, six months of infliximab treatment in patients with sarcoidosis led to signs of decreased CD4 + T cell alveolitis and decreased mastocytosis in the lungs of responders. Graphical Abstract: